Respuesta :

Answer:

Step-by-step explanation:

a). Let the missing term = a

   (a + 7) + (2x - 6) = -4x + 1

   (a + 2x) + (7 - 6) = -4x + 1

   (a + 2x) + 1 = -4x + 1

   (a + 2x) = -4x

   a = -4x - 2x

   a = -6x

   So the equation is,

  (-6x + 7) + (2x - 6) = -4x + 1

b). (a² + p + 1) - (q + 5a + r) = 4a² -2a + 7

   I have assumed p, q and r are the variables at the blank spaces.

   (a² - q) + (p - 5a) + (1 - r) = 4a² - 2a + 7

   By comparing both the sides of the equation,

    a²- q = 4a²

    q = a² - 4a²

    q = -3a²

    p - 5a = -2a

    p = -2a + 5a

    p = 3a

    1 - r = 7

    r = 1 - 7

    r = -6

    So the equation will be,

    (a² + 3a + 1) - (-3a² + 5a - 6) = 4a²- 2a + 7